Resilience in the face of peer victimization and perceived discrimination: the role of individual and familial factors - Fonseca de Freitas, DM; Mendonça, M; Wolke, D; Marturano, EM; Fontaine, AM; Coimbra, S (Elsevier, 2022)
Background Peer victimization and discrimination are two related forms of social victimization. However, the majority of studies only focus on one form or the other. This study investigates resilience in victims of both these forms of violence. Objective To identify individual and family level factors that foster, or hinder, resilience in the face of both peer victimization and perceived discrimination. Participants In a sample of 2975 high-school students, 22% (n = 644) met the criteria for substantial social victimization. The sample's mean age was 16.5 years, 57% were girls, 19% were in vocational courses, 12% were from an ethnic minority background, and 5% were lesbian, gay, or bisexual. Method A measure of resilience was created by regressing the mean levels of current mental health, self-esteem, and life satisfaction on the frequency of lifetime peer victimization and past year perceived discrimination. Regression analyses were conducted to identify correlates of resilience considering protective and vulnerability factors, including sociodemographic information, anxious personality, empathy, coping strategies, familial optimism, and the relationship with their mother and father. Results Resilience was associated with low anxious personality, four coping strategies (active, use of humor, low self-blame, low substance use), and satisfaction with the relationship with the mother. Conclusions Resilience is related to both behavioral and meaning-making coping strategies, personality traits, and satisfaction in relationships. This study's findings can be used to tailor interventions to foster resilience in adolescents exposed to social victimization.